Central nervous system haemorrhage causing early death in acute promyelocytic leukaemia - Borowska, Anna; Stelmaszczyk-Emmel, Anna; Pawelec, Katarzyna (Central European Journal of Immunology, 2015)
Acute promyelocytic leukaemia (APL) is a rare type of paediatric leukaemia characterised by a specific genetic mutation and life-threatening coagulopathy. The discovery of all-trans retinoic acid (ATRA), which acts directly on promyelocytic locus-retinoic acid receptor  (PML-RAR) gene product, brought a revolution to the therapy of this disorder. Unfortunately, despite an improvement in the complete remission rate, the early death (ED) rate has not changed significantly, and the haemorrhages remain a major problem. The most common bleeding site, which accounts for about 65-80% of haemorrhages, is the central nervous system. Second in line are pulmonary haemorrhages (32%), while gastrointestinal bleedings are relatively rare. Haemorrhages result from thrombocytopaenia, disseminated intravascular coagulopathy (DIC), and systemic fibrinolysis. Herein we present a boy aged one year and nine months with APL. The patient was not eligible for ATRA administration due to poor clinical condition. He developed bleeding diathesis that presented as disseminated intravascular coagulation (DIC) and led to intracranial haemorrhage, which resulted in the patient’s death.